Marseille et la Gaule méditerranéenne avant la conquête romaine - Sophie Collin Bouffier (Pallas, 2009)
Ever since the end of the VIIth century B.C., Marseilles represents a major if not unique stage in the relations between the Mediterranean and inland Gaul. The author intends to draw up an assessment of the Greek city and its evolution down to 49 B.C., the moment of its downfall at the hands of Caesar and to show how the relations between Marseilles and mediterranean Gaul underwent a change between the early IInd century and mid-Ist century under the growing influence of Rome through commerce in the first place, then through the direct interventions of her army. She will also deal with the future metropolis of western Mediterranean.